Análisis empírico de correlación entre el indicador de estructura de capital y el indicador de margen de utilidad neta en PYMEs; Empirical analysis of correlation between debt/equity ratio and the Net profit margin ratio in small and medium enterprises - Jhony Alexander Barrera Lievano; Sandra Patricia Parada Fonseca; Leidy Viviana Serrano Serrato (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2020)
– This research approach the financial results of the year 2017 of 2,622 companies of a capital city from Latin America with these the financial indicators of Capital structure and Net profit margin are calculated. The main objective is to determine whether there is a direct and significant relationship between the aforementioned financial indicators through the calculation of the Pearson correlation coefficient. A quantitative methodology is applied, of explanatory type, which seeks to identify patterns in the analyzed financial results that give light of the existence of an optimal general capital structure (relationship between the liability and equity). As a general conclusion, it is obtained that, with the data analyzed, there is no evidence that there is a direct and significant relationship between the indicators worked on. It remains as future research topics to carry out the same process, but by economic sectors and / or by company size.
Keywords: G32; 330; company; financing; correlation